Ποιοτικά χαρακτηριστικά εσπεριδοειδών που καλλιεργούνται στην Κύπρο - Σιακού, Μελπομένη (Department of Agricultural Sciences, Biotechnology and Food Sciences, Cyprus University of Technology, 2013)
Citrus fruits belong to the family of Rutaceae and they are an important family of fruit trees, widely known for their special nutritional value, the flavor and the aroma. In the Citrus belong a lot of different species, such as orange, lemon, lime and grapefruit. Citrus fruits are important for the human diet, due to their high nutritional value and antioxidant activity. Their fruits are rich in vitamin C, folic acid and other bioactive compounds, such as carotenoids, flavonoids, limonoids and phenols. These components are responsible for the prevention of cancer and other degenerative diseases. Citrus production in Cyprus occurs during the period between October-June. The main producing species of Citrus that are cultivated in Cyprus are the orange, the lemon, the grapefruit trees and also ‘Mandora’. ‘Mandora’ is an interspecific hybrid of mandarin and orange and is the main Citrus species grown in Cyprus. Moreover, in Cyprus they are cultivated other varieties of mandarin, such as ‘Nova’ and ‘Minneola’. During the last years, a great demand in red-fleshed grapefruit varieties such as the ‘Star Ruby’ and the seedless ‘White Marsh’ has emerged. In addition, the production of fruits from the ‘Valencia’ and other lemon varieties remains constant and are characterized by their thin peel and their juice rich in nutrients. The aim of this study was to define the quality characteristics of the Citrus fruits that are cultivated in Cyprus, by identifying the various chemical compounds and nutrients that they give them their characteristic properties. In addition, the main objective was to evaluate the fluctuations in the concentration of total soluble solids and total acids from the fruits of ‘Mandora’ tree, harvested during successive periods from different commercial orchards.
Keywords: Citrus fruits; Cultivation; Cyprus